Tripartite introductions of PGPR, humic acid, and N-fertilizer improve the growth and yield of sweet potato under glasshouse conditions - Sadeq, Buraq Musa; Ali Tan, Kee Zuan; Kasim, Susilawati; Alkooranee, Jawadyn Talib; Wong, Mui Yun; Othman, Nur Maizatul Idayu; Akter, Amaily; Chompa, Sayma Serine; Nabayi, Abba; Rahman, Md Ekhlasur (Universiti Kebangsaan Malaysia, 2024)
This study was undertaken to investigate the effects of plant growth-promoting rhizobacteria (PGPR) with humic acid (HA) as amendments on the morphological and physiological growth characteristics and yield of Sepang Oren sweet potato (Ipomoea batatas [L.] Lam). The experiment was conducted under glasshouse conditions at the Faculty of Agriculture, Universiti Putra Malaysia, for 110 days. Two factors were used in this experiment: The first factor was PGPR-HA inoculations (UPMB10, UPMRB9, and mixed strains) and non-inoculation-HA, and the second factor was the Nitrogen fertilizer levels (50, 75, and 100%). The treatments were replicated three times and arranged factorially in a randomized complete block design. The results showed that inoculations with PGPRs-HA (UPMRB9 and UPMB10 strains) positively affect the plant growth significantly (SPAD measurements, number of leaves, vine length, root length, leaf area index, root dry weight, shoot dry weight, and root: shoot ratio) of sweet potato upon addition of 50% and 75% of N-fertilizer, respectively. The nutrient content of soil and plant leaf significantly increased by 12-15% and 14-18%, respectively, compared to the uninoculated, when applied with the same inoculation. After 30 days, the population of soil bacteria increased, reaching a value of 8.65 log10 CFU/g soil. The use of PGPR-HA inoculations with N-fertilization resulted in a considerable rise in the majority of plant and soil parameters compared to the treatments without PGPR inoculation. Therefore, PGPR supplemented with humic acid (HA) may be considered a viable and sustainable strategy for enhancing sweet potatoes’ morphological and physiological attributes. This technique can result in increased crop productivity and serve as a substitute for nitrogen-based fertilizers.